De demonstrativa pronomina denna och den här och deras regionala varianter: en något kortare fallstudie - Radoev, Konstantin (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
The article examines the demonstrative pronouns denna and den här; their description in Swedish grammars is compared with their use in newspapers and the speech of both younger and older native speakers of the language. The norm and deviations from it are discussed as is the influence that the norm can have on the regional variants of the standard language.